Learners’ Engagement of Artificial Intelligence in Compliance of Formative Assessment Tasks in Mathematics - Dandoy, Jam Marie; Sibug, Angelika; Loreto, Anne Jasmin; Duran, Evangelyn; Baque, Sharmaine; Quintos Jr., Romeo (Indonesian Journal of Teaching and Learning, 2026)
Purpose – This study aims to evaluate junior high school students’ engagement in using Artificial Intelligence (AI) tools in formative assessment activities in Mathematics. The study is grounded in the growing integration of AI in education and the need to understand students’ engagement patterns to support an effective, responsible implementation. Methodology – A quantitative research design was employed. The respondents consisted of 112 junior high school students (55 males and 57 females) from Jose Rizal Institute–Orani, selected through simple random sampling. The sample size was determined using G*Power 3.1.9.4. A researcher-made questionnaire was used as the research instrument, and its validity and reliability were established using Cronbach’s Alpha. Data were analyzed using descriptive statistics, the Independent Samples T-test, and the One-Way Analysis of Variance (ANOVA). Findings – The findings revealed that the majority of students were slightly engaged in using AI tools for formative assessment tasks in Mathematics. A significant difference in AI engagement was observed by sex, with male students demonstrating higher engagement than female students. However, no significant differences were identified across grade levels, except in performance tasks and group activities, where Grade 7 students showed greater engagement. Novelty – This study provides original empirical evidence on students’ engagement with AI tools in formative assessment, highlighting differences by sex and specific assessment activities at the junior high school level. Significance – The findings benefit educators, school administrators, and policymakers by providing insights to inform the responsible and meaningful integration of AI into formative assessment and mathematics instruction.